Development and Validation of a New Method for Determination of Pb and Cr in Marine Organisms by Total Reflection X-Ray Fluorescence (TXRF) Spectroscopy - Blanca G. Beltrán; Ibiza Martínez-Serrano; Victor Ramos-Sanchez; David Chávez-Flores; Myrna C. Nevárez-Rodríguez; Emilio A. Suárez-Domínguez (Journal of Analytical Methods in Chemistry)
Lead and chromium contamination represents one of the most serious problems in the aquatic environments. The aim of this work was to develop and validate an accurate, sensitivity, and rapid method for the simultaneous determination of Pb and Cr at trace levels in tissues and fat of marine organisms such as turtle (Chelonia mydas), shark (Rhizoprionodon terraenovae), and dolphin (Tursiops truncatus), utilizing the total reflection X-Ray fluorescence (TXRF) spectroscopy. Working solutions were prepared in 10 mL of a solution 0.005 mol·L−1 EDTA and 1 mol·L−1 HNO3. In order to correct possible instrument drifts, 20 μg·L−1 of gallium was used as internal standard (IS). The results showed that TXRF method was linear over the concentration ranges of 5.242–100 μg·L−1 for Pb and 2.363–100 μg·L−1 for Cr. Limits of detection (LOD) achieved were 1.573 and 0.709 μg·L−1 for Pb and Cr, respectively, while limits of quantification achieved were 5.242 μg·L−1 for Pb and 2.363 μg·L−1 for Cr. The validated method was accurate and precise enough for determination of these heavy metals in samples of marine organisms as indicated by acceptable values of recovery between 90–101%. In addition, a certified reference material (BCR-279, sea lettuce) and a Centrum tablet were satisfactory analyzed, and the T-test for comparison of means revealed that there were no significant differences at the 95% confidence level between the values obtained with the proposed TXRF method and the certificated values. The repeatability of the method, expressed as relative standard deviation (RSD), was 5.1% and 4%, for Pb and Cr, respectively. In addition, other features of the developed method were a low sample volume of 10 μL, and the sample frequency achieved was 20 h−1.